2020
DOI: 10.22271/chemi.2020.v8.i1f.8292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management (INM) on nutrient uptake, yield and quality of potato (<em>Solanum tuberosum</em> L.)

Abstract: during rabi season of 2017-18 to evaluate the performance of potato under different integrated nutrient management (INM) options. The experiment was placed in randomised block design (RBD) with seven nutrient management options (T1-100% RDF, T2-100% RDF + yeast vinasse @ 2 t/ha, T3-75% RDF + yeast vinasse @ 2 t/ha, T4-50% RDF + yeast vinasse @ 2 t/ha, T5-100% RDF + vermicompost @ 2 t/ha, T6-75% RDF + vermicompost @ 2 t/ha, T7-50% RDF + vermicompost@ 2 t/ha) and replicated thrice. Results from the experiment ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Verma et al [25] explained the effect of INM practice in maize under maize-wheat cropping system that improvement of grain yield under application of vermicompost might be due to the betterment in soil physico-chemical properties (viz., pH, bulk density, infiltration rate and microbial biomass carbon) and availability of nutrients and organic carbon in optimum way, which reflected on growth and yield enhancing characters of maize. Besides vermicompost, the positive effect of yeast vinasse on nutrient uptake and yield was reported by Biswas and Dutta [11] in potato. Enhancement of yield might be due to the effective utilization of applied nutrients which increased sink capacity and higher nutrients uptake by crop.…”
Section: )mentioning
confidence: 83%
See 1 more Smart Citation
“…Verma et al [25] explained the effect of INM practice in maize under maize-wheat cropping system that improvement of grain yield under application of vermicompost might be due to the betterment in soil physico-chemical properties (viz., pH, bulk density, infiltration rate and microbial biomass carbon) and availability of nutrients and organic carbon in optimum way, which reflected on growth and yield enhancing characters of maize. Besides vermicompost, the positive effect of yeast vinasse on nutrient uptake and yield was reported by Biswas and Dutta [11] in potato. Enhancement of yield might be due to the effective utilization of applied nutrients which increased sink capacity and higher nutrients uptake by crop.…”
Section: )mentioning
confidence: 83%
“…Yeast vinasse, a by-product of bakery industries, can be a potential source of organic as it contains a substantial amount of nutrients. It is prepared through evaporation and drying of semi-liquid rejected part derived from reverse osmosis after anaerobic and aerobic microbial digestion of residual liquid part of yeast fermentation [11]. The inorganic sources of nitrogen, phosphorus and potassium were supplied through urea, SSP and MOP respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, promotes various physiological processes, improves plant nutrient uptake from vinasse (Table 2), and increases the rate of photosynthesis 72 . These factors contribute to improved vegetative growth by facilitating the translocation of assimilates into the reproductive parts of the plant, ultimately resulting in higher fruit yield potential 73 . However, the improvement in relative yield in the second season as opposed to the first year could be credited to the declining performance of the control treatment (0 g/l of PS and 0 l/m 3 of vinasse) in terms of vegetative growth, flower formation, and higher yield production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vinasse application enhanced the availability of soil phosphorus after crop harvest. Recently, 73 found that nutrient uptake (N, P, K) and quality indicators (carbohydrates and proteins) of potato tubers were higher with recommended fertilizer doses supplemented with 2 t/ha of vinasse.…”
Section: Discussionmentioning
confidence: 99%